ECOLOGICAL FEATURES OF SOAKING AND ASH PROCESSES IN THE PRODUCTION OF LEATHER - DANYLKOVYCH, Аnatolii; LISHCHUK, Viktor (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Ecological and colloid-chemical features of soaking-ash processes in processing of raw cattle leather materials at production of elastic leather for uppers of footwear according to operating and developed resource-saving technologies are investigated. To evaluate the effectiveness of the technological processes used a set of physic-chemical and operational properties of leather semi-finished products at different stages of its formation to the finished material.Resource-saving ecologically oriented technology of soaking and ash processes in leather production for shoe uppers from raw salted conserved materials - bull skins has been developed. Physicochemical, technological and ecological features of existing and developed technologies are studied. The developed technology due to the increase of process temperature provides more efficient use of chemical reagents, reduction of concentrations of environmentally hazardous reagents, process duration and energy consumption per unit of output. At the same time, the total consumption of chemical reagents is reduced by 2.2 times, and in the waste technological solutions the concentration of sodium sulfide and calcium hydroxide - by 2.9 and 4.4 times, respectively. However, the developed resource-saving environmentally friendly technology is characterized by a reduction in biological and chemical oxygen demand for the destruction of organic and inorganic substances in the waste soaking-ash solution after treatment of 1 ton of raw materials by 30.0 and 21.0%, respectively. By reducing the duration of the technological process by 2.3 times, the new technology can be considered as energy efficient. The developed resource-saving technology provides the formation of leather material for shoe uppers with an increased yield of 3.9%, and its performance properties meet the requirements of DSTU 3115-95. The results obtained in the development of environmentally friendly resource-saving technology of soaking ash processes for footwear leather uppers from raw cattle leather materials can be effectively used in the development of new innovative technologies for the manufacture of leather materials from a wide range of other raw materials.
Keywords: leather production; soaking and ash processes; ecologically oriented technology; resource-saving technology; leather properties